THE URGENCY OF UTILIZING THE NIAS LANGUAGE IN PRIMARY EDUCATION AS A FORM OF CULTURAL HERITAGE PRESERVATION - Darmawan Harefa (Universitas Nias Raya, 2026)
This study investigates the urgency of utilizing the Nias language in primary education in South Nias as a form of cultural heritage preservation. The research aims to examine how the integration of the Nias language into classroom instruction contributes to students’ understanding, cultural identity, and engagement in learning. A qualitative descriptive method was employed through interviews, classroom observations, and document analysis involving teachers, students, and community members. The findings reveal that the use of the Nias language in learning activities enhances students’ comprehension of instructional content, especially in early grades, as it bridges the gap between school knowledge and students’ daily experiences. In addition, the integration of local language strengthens students’ cultural awareness and pride in their heritage. The study also shows that students become more active, confident, and motivated when learning is delivered using their mother tongue alongside Indonesian. However, challenges such as limited teaching materials and lack of structured policy support still exist. Despite these challenges, the findings emphasize that the Nias language plays a crucial role in both improving educational effectiveness and preserving cultural identity. Therefore, the utilization of the Nias language in primary education is highly urgent and should be systematically supported to ensure sustainable cultural heritage preservation in South Nias.